The sheep in wolf's clothing - Lester, Helen (Houghton Mifflin, 2007)
Clothing is important to Ewetopia, but her carefully-chosen wolf outfit fails to impress the other sheep at the Woolyones' costume ball until a real wolf appears dressed as a sheep, mistakes her for his mother, and throws a tantrum when she outsmarts him.